Declining use of radical prostatectomy and pelvic lymphadenectomy despite more robotics: National population data over 15 years. Issue 2 (6th May 2019) - Roberts, Matthew J.; Papa, Nathan; Perera, Marlon; Joshi, Andre; Scott, Susan; Bolton, Damien; Lawrentschuk, Nathan; Yaxley, John
Abstract: Aim: To describe national surgical patterns of prostate cancer (PCa) care considering radical prostatectomy with or without pelvic lymphadenectomy and consideration of robotic‐assisted techniques. Methods: Retrospective analysis of publicly accessible Medicare claims data was performed for the period 2001–2016 and included patients undergoing radical prostatectomy with or without pelvic lymphadenectomy relative to total and PCa‐specific populations among men aged 45–84 years. Proportion of cases performed robotically was considered. Results: Total procedures performed increased from 2001, peaked in 2009 and subsequently decreased until 2016. Since 2009, the age‐specific rate of surgery in men aged 75–84 increased by 2.3‐fold, whereas the rates for men aged 55–64 and 45–54 reduced by 44% and 55%, respectively. Rates of concurrent pelvic lymphadenectomy fell until 2009 with subsequent stabilization (ratio 1.05–1.14) through to 2016. Significant regional practice patterns were observed, as was an increasing trend toward a robotic‐assisted laparoscopic approach, comprising more than 80% of radical prostatectomies in 2016. Conclusion: Since the peak in 2009, radical prostatectomy is performed less in men <65 years and more in men ≥65 years. An increasing proportion of cases omit concurrent pelvic lymphadenectomy and are performed robotically.